EKSPERIMENTASI MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) TERMODIFIKASI DITINJAU DARI KEMAMPUAN SPASIAL SISWA KELAS X SMA NEGERI KOTA SURAKARTA - Santosa, Santosa (Journal of Mathematics and Mathematics Education, 2012)
AbstractÂ This research is aimed: (1) To know which model among the MMP modified model, MMP model and the conventional model that produces a better student achievement. (2). To know which students who have better learning achievement among those who have high spatial ability, medium and low. (3). To know which model that produces better student achievement, the MMP modified modeI, MMP model or conventional model at each level of studentsâs spatial abilities.This is a quasi-experimental research design with a factorial 3 x 3. The research population is students of Grade X Senior High School Students Surakarta of the academic year 2010/2011. The sampling technique is a combination of studies stratified random sampling and cluster random sampling. The selected samples of this research are: (1). First experimental group consist of 99 studentâs (34 students of X1 class of SMA Negeri 2 Surakarta, 33 students of X1 class of SMA Negeri 3 Surakarta and 32 students of X5 class of SMA Negeri 8 Surakarta; (2). Second experimental group consist of 100 studentâs (34 students of X2 class of SMA Negeri 2 Surakarta, 34 students of X2 class of SMA Negeri 3 Surakarta and 32 students of X6 class of SMA Negeri 8 Surakarta; (3). Control group consist of 100 studentâs (34 students of X3 class of SMA Negeri 2 Surakarta, 34 students of X3 class of SMA Negeri 3 Surakarta and 32 students of X7 class of SMA Negeri 8 Surakarta.The instrument used for data collection is the preliminary ability tests, achievement tests and ability tests of spatial learning of students in the form of multiple choice. Before the test instruments are used, they are being tried out first. For preliminary ability and achievement test, the validity, reliability (used KR-20 test) and difference and difficulty level tests are tried out. While the instruments of spatial ability tests are taken from standardized tests so they do not need any try out. Before conducting the research first tested using a one-way Analysis of Variants with an unequal cell. Hypothesis of the research were tested by using a two-way Analysis of Variants with an unequal cell at the significance level of 5%. Previously, it is prerequisites tested, namely: normality test using the test Lilliefors and homogeneity test using Bartletts test.The conclusion of this research are: (1) The MMP modified learning model produce student achievement better than the MMP learning model and the conventional learning model, and the MMP learning model produces a better student achievementÂ  than conventional model; (2) The students who have high spatial ability are having better academic achievement than students who have medium and low spatial abilities, and students who have medium spatial abilities are having better academic achievement than students of low spatial ability; (3) On the students who have high spatial ability, the MMP modified learning model, the MMP learning model and conventional learning model produce similar student achievement. While the students who have medium and low spatial ability, the MMP learning modified model produce student achievement better than the MMP learning model and conventional learning model, and the MMP learning model produces student achievement better than the conventional learning model.Â Keywords: Learning Model, Missouri Mathematics Project, Spatial Ability.Â